Internalisasi Nilai-Nilai Pendidikan Akhlak Santri Melalui Pembinaan di Asrama Pondok Pesantren Abinnur Al-Islami Kelurahan Mompang Jae Kabupaten Mandailing Natal - Khairani, Fatimah; A, Alimir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research was motivated by the problems encountered such as there are still female students who are late for school, there are still female students who violate dormitory rules such as leaving the dormitory without the knowledge of the dormitory supervisor, not wearing socks, bathing outside the specified schedule, neglecting to perform prayers. congregation, there are even female students who still bring cellphones to the dormitory even though it is strictly prohibited in the dormitory. The aim to be achieved in this research is to determine the internalization of moral education values for female students through coaching at the Nazalal Huffadz Dormitory, Abinnur Al-Islami Islamic Boarding School, Mompang Jae Village, Mandailing Natal Regency.This research is qualitative research, the researcher uses descriptive type research, namely research that attempts to describe a symptom, event, incident that is happening right now.  The results of research regarding the internalization of moral education values for female students through coaching at the Nazalal Huffadz and Darul Qur'an dormitories show that there are three main stages. The first stage is the Value Transformation Stage, which is the process of providing knowledge to female students as the first step to internalizing the values of moral education. The next stage is the Value Interaction stage, where the ustadzah not only provides knowledge about the values of moral education, but also receives a positive response from the female students. The final stage is the Trans-Internalization of Values stage, where the ustadzah not only conveys knowledge and gets a good response, but also involves personality communication through example, conditioning and habituation to behave in accordance with the expected values.